Corporate Governance: Roots and Concept in Islamic Classical Literature (Al-Qamar, 2020)
Since, the inception of Islamic financial institutions, researchers have drawn attention to the topic of corporate governance in the context of Sharīʻah (Islamic Law). Owing to nascent in nature, the importance of governance is manifold for such institutions. Sharīʻah is not limited to religious rituals but it also deals with politics, social issues, economics, banking, contractual law and routine matters of one’s life. Therefore, whether the word governance is alien in Sharīʻah, or is it deeply rooted? We tried to address the question, to profoundly mine the classical and contemporary literature on conventional and Islamic mechanism of corporate governance. The concept of governance is deeply rooted in Islamic law. General principles of governance are found in the Quran, Ḥadīth, and in classical literature of fiqh. In the Quran, it is ordained to fulfill the obligations, deliver the trust, do justice, testify truth, and not to eat others’ property unjustly. In same lines, Prophet Muhammad ﷺ asked Muslims to show honesty, do not take things unlawfully, and everyone is responsible for his guardianship. Moreover, the concept of Shūra, mutual cooperation, Ḥisbah for accountability, Maqāsid-e-Sharīʻah, and legal maxims of Sharīʻah also provide guidelines to decision-makers for the protection of the rights of stakeholders. Hence, the concept of governance is not alien in Islam rather it is deeply embedded. This study might provide some comprehension to control, organize, and direct economic activities in the context of principles of governance in Sharīʻah.
Keywords: Corporate Governance; Sharīʻah; Maqāsid-e-Sharīʻah; Ḥisbah; Shūra; Legal Maxims